Development and application of a quadruplex real‐time PCR assay for differential detection of porcine circoviruses (PCV1 to PCV4) in Jiangsu province of China from 2016 to 2020. Issue 3 (28th September 2020) - Chen, Nanhua; Xiao, Yanzhao; Li, Xinshuai; Li, Shubin; Xie, Ningjun; Yan, Xilin; Li, Xiangdong; Zhu, Jianzhong
Abstract: To date, four species of porcine circoviruses (PCVs), including PCV1‐4, have been reported to exist in the clinical cases. Fast and effective differential detection is critical to monitor the infection and co‐infection status of PCVs for adopting reliable control strategies. However, currently available methods cannot simultaneously differentiate the four species of PCV strains. In this study, a quadruplex real‐time PCR assay based on TaqMan probes was developed for differential detection of PCV1‐4. The new quadruplex real‐time PCR assay exhibited satisfied specificity, sensitivity, repeatability and reproducibility. In addition, the new assay was applied to the detection of 120 clinical samples collected from 2016 to 2020 in Jiangsu province of China and compared with previously reported PCV1‐4 singleplex conventional PCR assays. Based on the clinical performance, the results from the quadruplex real‐time PCR and conventional PCR assays showed 100% agreement. A total of 47 samples were detected as PCV positive by the quadruplex real‐time PCR assay, including 1, 2, 1 samples were co‐infected with PCV1 and PCV4, PCV2 and PCV3, PCV2 and PCV4, respectively. Full‐length ORF2 sequencing and phylogenetic analysis supported the real‐time PCR results that 5, 34, 8 and 4 of the 51 PCV sequences were PCV1, PCV2, PCV3 and PCV4, respectively. This study provides a promising alternative tool for rapid differential detection of PCVs and confirms the coexistence of all species of PCV1‐4 strains in Jiangsu province in recent years.